Central exclusive production of J/[psi] and [psi](2S) mesons in pp collisions at √s=13 TeV - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; De Cian, Michel; Comerma-Montells, Albert; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gerick, David; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2018)
Measurements are reported of the central exclusive production of J/ψ and ψ(2S) mesons in pp collisions at a centre-of-mass energy of 13 TeV. Backgrounds are significantly reduced compared to previous measurements made at lower energies through the use of new forward shower counters. The products of the cross-sections and the branching fractions for the decays to dimuons, where both muons are within the pseudorapidity range 2.0 < η < 4.5, are measured to be σJ/ψ→μ+μ−=435±18±11±17 pbσψ(2S)→μ+μ−=11.1±1.1±0.3±0.4 pb.σJ/ψ→μ+μ−=435±18±11±17 pbσψ(2S)→μ+μ−=11.1±1.1±0.3±0.4 pb. \begin{array}{c}\hfill {\sigma}_{J/\psi \to {\mu}^{+}{\mu}^{-}} = 435 \pm 18 \pm 11 \pm 17\ \mathrm{p}\mathrm{b}\hfill \\ {}\hfill {\sigma}_{\psi (2S)\to {\mu}^{+}{\mu}^{-}} = 11.1 \pm 1.1 \pm 0.3 \pm 0.4\ \mathrm{p}\mathrm{b}.\hfill \end{array} The first uncertainties are statistical, the second are systematic, and the third are due to the luminosity determination. The cross-sections are also measured differentially for meson rapidities between 2.0 and 4.5. Good agreement is observed with theoretical predictions. Photoproduction cross-sections are derived and compared to previous experiments, and a deviation from a pure power-law extrapolation of lower energy data is observed. Open image in new window
Im Titel wird "psi" als griechischer Buchstabe dargestellt
The LHCb collaboration: R. Aaij, P. d'Argent, S. Bachmann, S. Braun, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Färber, D. Gerick, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, P. Krokovny, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, M. Neuner, A. Piucci, P. Seyfert, M. Stahl, S. Stemmle, J. van Tilburg, U. Uwer, A. Zhelezov [und weitere]
Gesehen am 04.06..2019